2007
DOI: 10.1128/ec.00331-06
|View full text |Cite
|
Sign up to set email alerts
|

cis -Acting Elements within the Candida albicans ERG11 Promoter Mediate the Azole Response through Transcription Factor Upc2p

Abstract: The azole antifungal drugs are used to treat infections caused by Candida albicans and other fungi. These drugs interfere with the biosynthesis of ergosterol, the major sterol in fungal cells, by inhibiting an ergosterol biosynthetic enzyme, lanosterol 14 ␣-demethylase, encoded by the ERG11 gene. In vitro, these drugs as well as other ergosterol biosynthesis inhibitors increase ERG11 mRNA expression by activation of the ERG11 promoter. The signal for this activation most likely is the depletion of ergosterol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 36 publications
4
53
0
Order By: Relevance
“…This can be explained by the similarity in azole compounds; these are substrates for multidrug efflux transporters that respond to ERG11 mutations (Andes et al, 2006;Song et al, 2004). Multiple resistance to azole antifungals was mainly associated with specific point mutations in the ERG11 gene (Marichal et al, 1999;Wang et al, 2009;Goldman et al, 2004), and was also associated with overexpression of the ERG11 gene and efflux pumps encoded by the CDR1, CDR2 and MDR1 genes (Hoot et al, 2008;Oliver et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the similarity in azole compounds; these are substrates for multidrug efflux transporters that respond to ERG11 mutations (Andes et al, 2006;Song et al, 2004). Multiple resistance to azole antifungals was mainly associated with specific point mutations in the ERG11 gene (Marichal et al, 1999;Wang et al, 2009;Goldman et al, 2004), and was also associated with overexpression of the ERG11 gene and efflux pumps encoded by the CDR1, CDR2 and MDR1 genes (Hoot et al, 2008;Oliver et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor Upc2 upregulates ERG11 expression in response to azoles and thereby contributes to azole resistance (534). Upc2 binds to the azole-responsive enhancer element (ARE), a region localized to two distinct 7-bp sequences at positions Ϫ224 to Ϫ251 in the ERG11 promoter (433). Both the ARE and Upc2 are necessary and sufficient for the azole induction of ERG11 (433).…”
Section: Alteration Of the Drug Targetmentioning
confidence: 99%
“…Upc2 binds to the azole-responsive enhancer element (ARE), a region localized to two distinct 7-bp sequences at positions Ϫ224 to Ϫ251 in the ERG11 promoter (433). Both the ARE and Upc2 are necessary and sufficient for the azole induction of ERG11 (433). Upc2 also binds to two distinct regions in its own promoter to autoregulate expression during azole exposure (229).…”
Section: Alteration Of the Drug Targetmentioning
confidence: 99%
“…One of the genes that is regulated by Upc2 is ERG11, a gene involved in ergosterol biosynthesis and the molecular target of the azole antifungals (15,22,43,61,62). Previous work demonstrated that lower ergosterol levels, caused by ergosterol biosynthesis inhibitors, such as azoles, have an inhibitory effect on hypha formation (63,64).…”
Section: Discussionmentioning
confidence: 99%